Bioclimatic rehabilitation of an open market place by a computational fluid dynamics simulation assessment. Issue 1 (24th August 2015) - Zoras, Stamatis; Dimoudi, Argyro; Evagelopoulos, Vasilis; Lyssoudis, Spyros; Dimoudi, Sofia; Tamiolaki, Anna-Maria; Stathis, Vasilis; Polyzakis, Apostolos; Deligiorgi, Euterpi
Abstract: These days urban design of open spaces is strongly related to bioclimatic techniques and practices. It is here presented the procedure of a bioclimatic study by the use of simulation tools. The area of an open market place is characterized of decreased human thermal comfort conditions during summer time. The employment of computational fluid dynamics has contributed in the understanding of what interventions should be made at the open space in order to succeed the defined thermal related targets. Table of the proposed rehabilitation explains what the interventions would contribute in the improvement of the local environment.